The EU long-term strategy to reduce GHG emissions in light of the Paris Agreement and the IPCC Special Report on 1,5°C - Jakob Wachsmuth; Michiel Schaeffer; Bill Hare (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2018)
The European Commission's long-term Strategic Vision "A clean planet for all" and the In-Depth Analysis supporting it were released on 28 November, 2018. The Commission claims that an 80% reduction of the EU's GHG emissions by 2050 can be taken as being in line with the Paris Agreement's long-term temper-ature goal (LTTG). This is shown to be questionable due to the Commission's re-labelling of the former "hold-below-2°C" pathways associated with the 2010 Can-cun Agreements as "well-below 2°C" pathways. Those "hold-below-2°C" path-ways had a 66% chance of limiting warming to 2°C and were further characterised by a peak warming of around 1.7-1.8°C. By contrast, the actual Paris long-term temperature goal is, by design, a strength-ening of the former "hold-below-2°C" goal. In this paper, strong arguments are provided that this implies achieving a lower peak warming and a higher probability of limiting warming to 2°C. Further, the "hold-below-2°C" pathways do not provide guidance in terms of lowering peak warming and increasing the probability of lim-iting warming to 1.5°C, an integral part of the Paris LTTG (unless with negative emissions at a scale the IPCC Special Report on 1.5°C does not deem feasible). At the same time, the IPCC SR1.5 is very clear about the increases in climate risks between 1.5°C and 2°C, which relates to the clause of the LTTG that holding warming well below 2°C significantly reduces the risks and impacts of climate change. This provides a clear argument for lower limit to peak warming. Despite the shortcoming with regard to interpreting "well-below-2°C", the EU Strategic Vision is a clear shift away from the lower end of the former "80-95%" re-duction target by 2050 towards achieving net-zero greenhouse gas emissions in 2050. This is based on the In-Depth Analysis, which shows that a greenhouse gas emission reduction of 90% by 2050 compared to 1990 is necessary to keep 1.5°C in range, while limiting negative emissions even calls for net-zero green-house gas emissions in 2050. Hence, the "net-zero greenhouse gas emissions in 2050" target chosen in the Strategic Vision is a reasonable choice in light of the Paris Agreement and the IPCC Special Report on 1.5°C, but 80% reduction by 2050 is not. Thus, the lower end of the current "80-95%" EU target is insufficient.
urn:nbn:de:0011-n-5250734
Keywords: 330